Materialist Intersectionality and Situated Critical Genealogies. Towards an Epistemic-Political Rupture - Parra, Valeria Fabiana (2022)
In this paper, I argue that the critical capacity of the intersectional perspective is enhanced when it is articulated with the materialist perspective that involves a particular type of practice. This practice read social processes as part of a complex whole structure with tensions, ambiguities, and contradictions. It intervenes conceiving theory and practice as inseparable. Facing fragmented, simplistic, additive and unidimensional analyses centered on a single axis of oppression, the articulation between both critical perspectives has the power to address the multiple oppressions in a complex way, within the framework of contradictory and unequal social formations. I emphasize that the potential of the articulation between both critical perspectives is requiring the recovery of critical genealogies, which is able to explain the knotting between body and politics in opposition to the dichotomous logic that insists on separating them. Furthermore, the mapping of critical genealogies allows us to revitalize intersectional analysis - in the context of the processes of neutralization and simplification that annul the concept and to show its political core Materialist intersectionality and situated critical genealogies. Towards an epistemic-political rupture in the practical background. This challenge the deterministic readings that invalidate struggles and resistances; to move on to the epistemic and political recognition of the knowledge produced from the margins.